Cost evaluation for 12-storey reinforced concrete apartment building in Sabah due to seismic design - Nur Shairah, Zulkhibri; Hanis Athirah, Roslan; Mohd Irwan, Adiyanto (2022)
In June 2015, Ranau stated earthquake of moment magnitude M 6.1 which cause a lot of damage to buildings. Therefore, seismic design input should be applied for new buildings to minimize damage. This work investigates the influence of seismic design on structural works cost. A 12W storey apartment reinforced concrete apartment has been used as a model for the project. In this research, soil type D and 3 levels of seismicity were used as design variables. The reference peak ground acceleration, αg used were 0.08g, 0.12g and 0.16g. The results indicate that models with seismic design have greater structural costs, increasing 3.4% to 19.1%.